MATHEMATICAL DISPOSITION ANALYSIS OF ELEMENTARY SCHOOL STUDENTS ON THEIR MATHEMATICAL PROBLEM-SOLVING SKILL - Riandi Marisa; Yulia Santi; Ety Mukhlesi Yeni; Sri Dewi Nirmala (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The role of students' attitudes (disposition) towards mathematics is an important element in solving their mathematical problems and must be maximized properly. Disposition has the following indicators such as self-confidence, flexibility, persistence, curiosity, reflecting, and applying it. This paper describes the elementary students' mathematical disposition profile toward their problem-solving skills. The research method uses qualitative-descriptive. Data were collected through questionnaires, observations, and interviews, which were subsequently analyzed by triangulation technique. The results indicate that there is a significant relationship between elementary school students' mathematical dispositions and their problem-solving skills. Students who achieve the "excellent" category of mathematical disposition indicators (mathematical disposition indicators score > 85%) have good problem[1]solving skills. Furthermore, students who are categorized as "less" (mathematical disposition indicators score < 60%) have problem-solving skills and need treatment. The analysis results that were obtained through questionnaires, observation, and confirmation with interviews indicate that the students' mathematical disposition skills in group A were categorized as excellent with disposition indicators of 95%. Students’ mathematical disposition in group B was categorized as quiet good with the students' mathematical disposition criteria of only 65%. In addition, students’ mathematical disposition in group C was categorized as less good because students' mathematical disposition skills appear only 65%.